Effectiveness of Mammography Boot Camp for Radiology Residents - Keum Won Kim; Eun Hye Lee; Jin You Kim; Young Mee Park; Hae Jung Kim; Eun Jung Choi; Kyung Hee Koh; Youme Kim; Hye-Won Kim; Sang Yu Nam; Bobae Choi; Kyu Sun Kim; et al. (대한영상의학회지, 2017)
Purpose To evaluate an educational effect of the mammography boot camp (MBC) for radiology residents and analyze affecting factors.